Sustainable food and agriculture : an integrated approach - Campanhola, Clayton; Pandey, Shivaji (Academic Press, an imprint of Elsevier : FAO, Food and Agriculture Organization of the United Nations, 2019)
"Sustainable food and agriculture: an integrated approach" is the first book to look at the imminent threats to sustainable food security through a cross-sectoral lens. As the world faces food supply challenges posed by the declining growth rate of agricultural productivity, accelerated deterioration of quantity and quality of natural resources that underpin agricultural production, climate change, and hunger, poverty and malnutrition, a multi-faced understanding is key to identifying practical solutions. This book gives stakeholders a common vision, concept and methods that are based on proven and widely agreed strategies for continuous improvement in sustainability at different scales.